Damaging of tungsten and tungsten–tantalum alloy exposed in ITER ELM-like conditions. (December 2016) - Makhlai, V.A.; Garkusha, I.E.; Linke, J.; Malykhin, S.V.; Aksenov, N.N.; Byrka, O.V.; Herashchenko, S.S.; Surovitskiy, S.V.; Wirtz, M.
Abstract: The damage of deformed double forged pure tungsten (W) and tungsten alloyed with 5 wt% tantalum (WTa5) have been studied in experimental simulations of ITER-like transient events with relevant surface heat load parameters (energy density up to 0.75 MJ/m 2 and the pulse duration of 0.25 ms) as well as particle loads (varied in wide range from 10 23 to 10 27 ion/m 2 s) with quasi-stationary plasma accelerator QSPA Kh-50. The plasma exposures were performed for the targets maintained at room temperature and preheated at 200 °C. The surface heat loads were either with no melting of W surface or above the melting threshold. The development of surface morphology of the exposed targets as well as cracking and swelling at the surface is discussed. Surface analysis was carried out with an optical microscopy and SEM. Surface modification and development of cracks led to increases of roughness of exposed surfaces. X-ray diffraction (XRD) has been used to study the micro-structural evolution of the exposed targets. The micro deformations of W and WTa5 are similar for targets exposed under similar conditions. The contribution of excess complexes of interstitial atoms in the formation of cracks after plasma irradiation was evaluated.